In silico studies on potential MCF-7 inhibitors of alkaloid and phenolic compounds isolated from Zanthoxylum nitidum: A combination of molecular docking and admet analysis - Thi Tuyen, Tran; Cao Bach, Pham; Viet Hai, Ha; Thi Hong Minh, Pham; Thi Hong Van, Nguyen; Minh Quan , Pham (Vietnam Journal of Science and Technology, 2023)
Cancer is one of the leading cause of death worldwide that cause a burden for the health system and economic of both developed and developing countries. Tubulin is a wellknown biochemical target in the field of cancer drug discovery. The inhibition of tubulin-microtubule dynamics would result in the mitosis during cell division, thus, killing the cancerous cells. To date, there have been some tubulin targeting drugs have been developed including paclitaxel and the vinca alkaloids, however, treatments are not high ineffective and efforts to discover new molecules are still in urgent needed. In this study, computational molecular simulation and assessment of drug-like properties were used to gain insights into the binding ability of 16 alkaloid and phenolic compounds isolated from Zanthoxylum nitidum on tubulin protein. Among studied candidates, compounds 8 and 10 were identified as potential candidates for inhibiting the function of tubulin at the active site regarding binding affinity, dock pose and ADMET properties analysis. These findings shed light on the anti-cancer potential of compounds isolated from Zanthoxylum nitidum.